PENGEMBANGAN MODUL EDUKASI KELUARGA ANAK JALANAN DI KAWASAN LAMPU MERAH TABEK GADANG PEKANBARU - Anhar, Salsabila Awalia; Yakub, Elni; Saam, Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study discusses the content or material of street children's education modules and discusses the feasibility or validity of street children's education modules. Compiled material about street children's family education module which is reviewed from the clarity of the material, systematic material, pictures of support, the compatibility of the delivery time of the material and the completeness of the material. The module is validated by 4 validators consisting of 2 BK lecturers (material experts) and 2 BK teachers (collecting). This research uses Research and Development (R&D) research methods. After the revision was approved and followed the suggestions given, the results obtained from the validator's assessment stated that each quality of the material aspects that had been prepared, namely the calculation results for the material clarity aspect obtained a value of 4.5 with a percentage of 90% which is included in the category of Very Clear , for systematic aspects the material obtained a value of 4.0 with a percentage of 80% included in the Systematic category, for the aspect of image support a value of 4.25 with a percentage of 85% included in the category of Very supportive, for the aspect of time suitability in the delivery of material obtained a value of 4.0 with a percentage of 80% included in the Suitable category, for aspects of completeness the material obtained a value of 4.25 with a percentage of 85% included in the Very Complete category, while for all aspects of the 4.2 value included in the Good category.Key Words: Education Module, Families of Street Children